De historia e historiadores : homenaje a José Luis Romero - Bagú, Sergio, 1911-2002 (Historia (Siglo Veintiuno Editores), 1982)
Particiapan: Sergio Bagú, Gregorio Weinberg, Leopoldo Zea, Rafael Gutiérrez Girardot, Luis González, Tulio Halperín Donghi, Arturo Ardao, Malcom Deas, Juan Marichal, Alberto Tenenti, Jorge E. Hardoy, Richard M. Morse, Nicolás Sánchez Albornoz, Juan Antonio Oddone, John Linch, Roberto Cortés Conde, James R. Scobie, Ezequiel L. Gallo, Alberto Ciria, Leandro H. Gutiérrez.